Alcohol‐Related Consequences Among First‐Year University Students: Effectiveness of a Web‐Based Personalized Feedback Program. Issue 2 (July 2014) - Doumas, Diana M.; Nelson, Kinsey; DeYoung, Amanda; Renteria, Camryn Conrad
<x xml:space="preserve">Abstract</x> This study evaluated the effectiveness of a web‐based personalized feedback program using an objective measure of alcohol‐related consequences. Participants were assigned to either the intervention group or an assessment‐only control group during university orientation. Sanctions received for campus alcohol policy violations were tracked over the academic year. Results indicated high‐risk drinkers in the control group received significantly more sanctions than other students. Results support the effectiveness of web‐based interventions.